Development of breast muscle parameters, glycogen reserves, and myogenic gene expression in goslings during pre- and post-hatching periods - Dang, De Xin; Zhou, Haizhu; Lou, Yujie; Liu, Xiao; Li, Desheng (Frontiers in Physiology, 2022)
This study aimed to better understand the development patterns of breast muscle and glycogen reserves in goslings during pre- and post-hatching periods. The timepoints for sampling were embryonic day 23 and 27, day of hatch, and day 1, 4, and 7 post-hatching. We found that the body weight of goslings increased with age. The small intestine developed with age and remained reasonably constant on day 4 post-hatching. The breast muscle development decreased with age and kept relatively stable on day 1 post-hatching. The diameter of myofiber increased prior to hatching and then decreased while hatching. The development patterns of breast muscle glycogen reserves were similar to the diameter of myofiber. In contrast, the contents of liver glycogen began to decrease before hatching, and then increased rapidly after hatching. Moreover, the expression of Myf-5 increased with age. The expression of MSTN was maintained at high levels prior to hatching, and dropped immediately after hatching, and then gradually increased with age. Additionally, we also observed that the glycogen content in breast muscle was positively correlated with the diameter of myofiber. The liver glycogen content was positively correlated to the relative weight of breast muscle, diameter of myofiber, and breast muscle glycogen contents. The development pattern of myofiber was synchronized with the change of MSTN/Myf-5 ratio. This study provided a profile to understand the development patterns of breast muscle, glycogen reserves, and myogenic gene expression in goslings, which was beneficial to understand the characteristics of energy reserves during the early life of goslings.